2021
DOI: 10.7196/samj.2021.v111i8.15489
|View full text |Cite
|
Sign up to set email alerts
|

The HIV cascade of care among serodiscordant couples in four high HIV prevalence settings in sub-Saharan Africa

Abstract: HIV-negative individuals in a serodiscordant relationship are at high risk of HIV transmission. This risk of infection may increase if: (i) the partner living with HIV is not aware of their HIV status; [1,2] (ii) the partner living with HIV is not on antiretroviral therapy (ART), and therefore has an unsuppressed viral load (VL); and (iii) the couple is practising unsafe sex. Serodiscordant couples are thought to be a major source of HIV transmission in the sub-Saharan Africa region, [3] with studies estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In addition, four prevalence surveys conducted in Ndhiwa (Kenya), Chiradzulu (Malawi), Gutu (Zimbabwe) and Nsanje (Malawi), found an overall prevalence of 10.9% [26]. These estimates were comparable to the population-based AIS study in Uganda and lower than the estimate from our study.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In addition, four prevalence surveys conducted in Ndhiwa (Kenya), Chiradzulu (Malawi), Gutu (Zimbabwe) and Nsanje (Malawi), found an overall prevalence of 10.9% [26]. These estimates were comparable to the population-based AIS study in Uganda and lower than the estimate from our study.…”
Section: Discussionsupporting
confidence: 66%
“…Comparing to other settings, the prevalence of HIV serodifference among couples estimated from a population-based survey in Kenya was 5.8% [25]. In addition, four prevalence surveys conducted in Ndhiwa (Kenya), Chiradzulu (Malawi), Gutu (Zimbabwe) and Nsanje (Malawi), found an overall prevalence of 10.9% [26]. These estimates were comparable to the population-based AIS study in Uganda and lower than the estimate from our study.…”
Section: Discussionmentioning
confidence: 99%
“…The UNAIDS ( 2021 ) reported that in 2020, 65% of all new infections were from key populations and their partners. In addition, Chihana et al ( 2021 ) indicate that HIV-serodiscordant couples contribute 30% of all new infections in sub-Saharan Africa. Related to this, Ayele, Tegegne, Damtie, Chanie, and Mekonen ( 2021 ) state that heterosexual transmission within serodiscordant relationships is one of the major sources of new HIV infections, however, there is low condom use among these couples.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing to other settings, the prevalence of HIV serodifference among couples estimated from a population-based survey in Kenya was 5.8% [25]. In addition, four prevalence surveys conducted in Ndhiwa (Kenya), Chiradzulu (Malawi), Gutu (Zimbabwe) and Nsanje (Malawi), found an overall prevalence of 10.9% [26]. These estimates were comparable to the population-based UAIS study in Uganda [22] and lower than the estimate from our study.…”
Section: Discussionmentioning
confidence: 87%